NHC-gold compounds mediate immune suppression through induction of AHR-TGFβ1 signalling in vitro and in scurfy mice - Cheng, Xinlai; Häberle, Stefanie; Shytaj, Iart Luca; Ghafoory, Shahrouz; Bauer, Andrea; Hoheisel, Jörg D.; Fackler, Oliver Till; Lusic, Marina; Hadaschik, Eva; Wölfl, Stefan (Communications biology, 2020)
Cheng, Haeberle et al. identify NHC-gold complexes as ligands of the aryl hydrocarbon receptor, which triggers TGFβ production for immune suppression. They find that the MC3 compound activates TGFβ signalling while reducing Il-2 expression and CD4+ T-cell activation and suppresses autoimmune phenotypes in a mouse model of IPEX syndrome.